Factors Influencing Local Government Financial Performance - Wiwik Andriani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to examine: The effect of local revenue, balancing funds, and capital expenditures on the financial performance of local governments. The population in this study were all local governments in West Sumatra Province, which consisted of 19 regencies and cities. The sample in this study amounted to 19 districts/cities. The data analysis techniques are descriptive statistics, multiple regression analysis, classical assumption test, hypothesis test, and R square test. The results showed that: regional income has a negative effect, the balanced fund has no effect, and capital expenditure has no impact on the financial performance of local governments.